Tahlil Akhta' As Shautiyah fi Ta'diyatil al Mafsil lada Thullab al Jamiah Ali bin Abi Thalib al Islamiyyah Bisurabaya - Fakhlipi, Muhammad Rafeli; Al-Bathoty, Farid; Nasaruddin Idris Jauhar (Al Intisyar: Jurnal Pendidikan Bahasa Arab, 2023)
The causes of difficulties in Arabic are ignorance of the rules or customs of the language, the influence of the mother tongue, and inaccurate language teaching. This study aims to identify vocal errors in the use of pauses in Arabic by semester I students majoring in Arabic language education at Islamic University Ali bin Abi Thalib Surabaya. The method used is a qualitative one, namely descriptive analysis, which explains the data and summarizes it in words. Data collection techniques were carried out using free listening and speaking techniques, writing techniques, and recording techniques using a voice recorder. The results of this study indicate that there are three mistakes that are often made by students when using pauses in Arabic, namely that first, students read texts with pauses but do not read in a high tone before pauses (52.4%). Second, students read the text with pauses but not at the proper pauses (33.3%). Third, there was no pause at all in students' pronunciation while reading the text (14.3%). The results of this study provide an overview of phonological errors in the use of pauses in Arabic so that they can be used as a reference for evaluation in learning Arabic.